A case report of double positive peripheral T cell lymphoma- not otherwise specified in a young pregnant female - Nishi Trivedi; Jigna Padhiyar; Nayan Patel; Sanjay Gandhi (Wolters Kluwer Medknow Publications, 2022)
Peripheral T-cell lymphoma (PTCL) comprises 5-20% of all non-Hodgkin lymphomas (NHL). These all have different morphological patterns, phenotypes, and clinical presentations making it a diverse group of lymphomas. PTCL, not otherwise specified (PTCL-NOS), is a subtype considered to have a poor prognosis and a low overall survival rate of only about 30-40%. We report a case of primary cutaneous PTCL-NOS presenting in a young pregnant female with multiple progressive, tender, and necrosed nodules all over her body for 3 months. Her skin biopsy findings led us to suspect malignancy, and via immunohistochemistry (IHC), her diagnosis was confirmed. Cutaneous lymphoma is a dangerous albeit rare entity and should be kept in mind when the commoner differentials have been ruled out.